In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L. (Whaling and History II : new perspectives, 2006)
In 1970 the fourth and final volume of Arne Odd Johnsen and Joh. N. Tønnessens’s Den moderne hvalfangsts historie was published. The work represented a milestone in the writing about the development of the 20th century whaling industry. This paper reviews the literature that has been published in Norway and internationally on the history of modern whaling after Johnsen and Tønnessen, and analyses the focus, trends and direction in the research and writing on whaling history in the period.
Keywords: Antarktis; Sørishavet; hvalfangstindustri; litteratur; pelagisk hvalfangst

The black book of 1913 - a means of disciplining whaling employees - Børresen, Dag Ingemar (Whaling and History II : new perspectives, 2006)
Keywords: Nordmenn; Sørishavet; arbeidsforhold; hvalfangere; pelagisk hvalfangst

Norwegian-Japanese whaling relations in the early 20th century : a case of successful technology transfer - Mageli, Eldrid (Scandinavian Journal of History, 2006)
Keywords: Japan; Norge; Sørishavet; hvalindustri; pelagisk hvalfangst

Bjarne Aagaard and his Crusade against Pelagic Whaling in the late 1920s - Ringstad, Jan Erik (Whaling and History II : new perspectives, 2006)
Keywords: Norge; Sørishavet; historie; hvalfangst; pelagisk hvalfangst

Kval i sikte - frå fjellbygda : nokre blad or soga om kvalfangarane i Rauland og Vinje - Landsverk, Helga; Kjelingtveit, Tone Liv; Bylander, Olof; Henriksveen, Herman (Rauland historielag, 2001)
Keywords: Nordmenn; Sørishavet; historie; hvalfangere; pelagisk hvalfangst